Світлоглиняні вузькогорлі амфори «інкерманського» типу - Кропотов, В.В. (Археологія, 1998)
Стаття присвячена класифікації світлоглиняних вузькогорлих амфор «інкерманського» типу, які датуються рубежем III—IV— початком V ст. Статья посвящена классификации светлоглиняных узкогорлых амфор «инкерманского» типа, датируемых с учетом последних находок рубежем III—IV вв. — началом V в. На основании анализа форм изделий предложено их разделение на три варианта. Опираясь на хронологию крымских комплексов, автор датирует образцы варианта 1 первой половиной — серединой IV в., варианта 2 — второй половиной IV в., а варианта 3 — концом IV — началом V вв. The paper is devoted to classification of light-clay narrow-neck amphoras of the «Inkerman» type, dated (with allowance for latest findings) to the period between 3d-4th and early 5th centuries. Proceeding from the analysis of shapes of amphoras it is suggested to divide them into three variants. Basing on the chronology of Crimean assemblages, the author dates amphoras of the 1st variant the first half and mid of the 4th century, those of the second variant — the second half of the 4th century, the 3d variant — the end of the 4th and early 5th century.